The dual nature of the tidal tails of NGC 5904 (M5) - Piatti, Andres Eduardo (2023)
The tangential velocity dispersion of stars belonging to the Milky Way globular clus-ter’s tidal tails has recently been found from N-body simulations to be a parameterthat distinguishes between cored and cuspy profiles of low-mass dwarf galaxy darkmatter subhaloes where that globular cluster formed, and the in-situ formation sce-nario. In this context, we discovered that M5’s tidal tails are composed by stars at twodifferent metallicity regimes ([Fe/H] ∼ -1.4 dex and -2.0 dex). The more metal-richtidal tail stars are of the same metal content than M5’s members and have a tangen-tial velocity dispersion that coincides with the predicted value for a cuspy formationscenario (subhalo mass ∼ 10 9 M ). The more metal-poor stars, that are found alongthe entire M5 tidal tails and have similar distributions to their more metal-rich coun-terparts in the M5 colour-magnitude diagram and orbit trajectory, have a tangentialvelocity dispersion that refers to a cored subhalo (mass ∼ 10 9 M ) or an in-situ for-mation scenario. In order to reconcile the dual distribution of M5 tidal tail stars, inkinematics and chemistry, we propose that M5 collided with another more metal-poorand less massive globular cluster anytime before or after it was accreted into the MilkyWay.